From Folk to Professional: The Art of Bengal at the Crossroads - Karlova, Evgenia M. (Actual Problems of Theory and History of Art, 2019)
The Indian popular prints have so far attracted little attention from Russian researchers, although they are represented in the collections of the State Museum of the History of Religion, the Pushkin Museum of Fine Arts, the Tretyakov Gallery. The State Museum of Oriental Art has recently acquired an album of Calcutta chromolithographs, whose story is quite indicative. Initially, it was kept in the main museum collection, but was later moved to the library’s vault — its artistic qualities were assessed as unworthy of the museum collection. Now, when the study of folk and popular art is becoming more relevant, it is necessary to give a new assessment of the aesthetics of these things. This assessment should be based on the sociohistorical context in which chromolithographs were created. Calcutta is a unique art center in 19th-century India where synthetic culture was formed, reflecting both native Indian and colonial aesthetics. A short but vivid history of the existence of the popular paintings and prints of Calcutta — kalighat, battala woodcuts, and then chromolithographs, prepared the ground for the formation of a unique modern popular culture of this country. The evolution of artistic techniques and iconography in Calcutta chromolithographs helps to trace the evolution of the national identity of Indian artists.